Elements of rhythm in apparatus movements: training gymnasts - Suprun, A. A.; Medvedeva, E. N.; Vlasova, N. Yu.; Borisova, V. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to based on the evaluation of the impact of electrical stimulation of the primary muscle groups and the kinematic characteristics of movements during the execution of technical maneuvers with an object to music with varying rhythmic patterns, we aim to determine the focus of subject training in rhythmic gymnastics.